TRAINING IN MAKING LEARNING VIDEOS FOR TEACHERS IN CLINCING DISTRICT, NORTH JAKARTA - Robinson Situmorang; Jhoni Lagun Siang; Beatrix J.M Salenussa (Peneliti.net, 2019)
Purpose of this research is training in making video learning that can be used by teachers in the learning process. The targets in this study were all teachers in junior high schools in Clincing sub-district, North Jakarta. Considering this training is in the form of making learning videos, the research method used is research and development (R&D). The teachers in Clincing sub-district, North Jakarta were very enthusiastic in participating in this training. They are very grateful because with this training they can make learning videos that are used in the learning process